2016
DOI: 10.1016/j.jad.2016.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disorders and falls among older adults

Abstract: Background:Falls are common among older adults and can lead to serious injuries, including fractures. We aimed to determine associations between anxiety disorders and falls in older adults. Methods:Participants were 487 men and 376 women aged ≥60 years enrolled in the Geelong Osteoporosis Study, Australia. Using the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Non-patient edition (SCID-I/NP), lifetime history of anxiety disorders was determined. Falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
(15 reference statements)
2
13
0
Order By: Relevance
“…This might be fruitful, because the majority of aged individuals have regular GP visits in Germany. 50 In addition, it has been shown that the general psychological factors used in the present study are potentially modifiable, which might be essential for creating interventions. 48 For example, a recent study (randomized controlled trial) examined the effectiveness of an intervention (series of cognitive-behavioral sessions) targeting to reduce FOF.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This might be fruitful, because the majority of aged individuals have regular GP visits in Germany. 50 In addition, it has been shown that the general psychological factors used in the present study are potentially modifiable, which might be essential for creating interventions. 48 For example, a recent study (randomized controlled trial) examined the effectiveness of an intervention (series of cognitive-behavioral sessions) targeting to reduce FOF.…”
Section: Discussionmentioning
confidence: 88%
“…48 However, further research is required due to some methodological constraints in existing studies. 50 In addition, it has been shown that the general psychological factors used in the present study are potentially modifiable, which might be essential for creating interventions. [25][26][27][28][29] Longitudinal studies are required to reveal insights into the temporal relationship between psychological factors and FOF.…”
Section: Discussionmentioning
confidence: 88%
“…For instance, to date very little or no research has examined the association between anxiety and global attachment style, residents’ sense of mastery (i.e., personal control and sense of competence in mastering one’s day-to-day activities and environment), level of social engagement (i.e., having connections with others and being involved in group activities), or experience of a fall. Previous late-life research examining these variables have found significant associations between depression and lower levels of mastery (Davison, McCabe, Knight, & Mellor, 2012) and social engagement (Kang, 2012; Resnick, Fries, & Verbrugge, 1997) among RACF residents, whereas community-based studies have found an association between anxiety and the experience of a fall (Holloway et al, 2016; Menant et al, 2013) and an anxious attachment style (Kafetsios & Sideridis, 2006). Given that attachment behavior continues throughout the life span and impacts on well-being (Bowlby, 1980), and RACF residents are at particular risk of low social engagement, low perceived mastery, and increased risk of falls, research examining these factors and their association with anxiety is warranted.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, abnormal bone metabolism is a common symptom of stress and anxiety [10,11]. Clinical studies have shown that the probability of osteoporosis and fractures in patients with anxiety and depression is significantly higher than that in normal controls [12][13][14], suggesting that an individual's anxiety state is closely related to bone metabolism. Although evidence indicates that anxiety can affect bone loss, the underlying neural mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%